Systematics of means of vibration isolation in technogenic systems - P. D. Balakin (Омский научный вестник)
The periodic nature of natural and man-made processes, the parametric properties of objects and the physical laws of interaction of material bodies and media affect non-useful vibrations of mechanical systems. Vibrations of small amplitude and high frequency are called vibrations, the weakening or elimination of which form a system of vibration protection of machines, part of which is vibration isolation. Decomposition of the General problem of vibration isolation helps to choose technical and engineering solutions of vibration isolation devices for basic, inter-unit connections, and for personnel. The article is intended for developers of vibration isolation tools, students, postgraduates and researchers whose interests include machine dynamics, vibration protection and vibration isolation of machines.